Wo ke yi liu xia ta ma? = Can I Keep Him - Brown, Peter, 1979-; Qi, Yangping (Guiyang shi : Guizhou ren min chu ban she, 2022)
When Lucy, a young bear, discovers a boy lost in the woods, she asks her mother if she can have him as a pet, only to find him impossible to train.
Original title: Children make terrible pets.
Text in simplified Chinese scripts.
Keywords: Pets -- Juvenile fiction; Bears -- Juvenile fiction; Missing children -- Juvenile fiction; Chinese language materials; Picture books